Correlates of private security officers’ job satisfaction in South Korea - Paek, Seung Yeop (International journal of comparative and applied criminal justice, 2022)
This exploratory research examines the determinants of private security officer’s job satisfaction. Despite the growing private security industries and their influence on security governance around the world, little is known about private security officers’ attitudes towards their work. In order to fill this gap, 436 in-house and contract security officers are analysed in the cultural context of South Korea. The impacts of job and organisational characteristics on job satisfaction are examined, and a subgroup analysis is performed to assess the differences in the predictors of job satisfaction between in-house and contract officers.